2010
DOI: 10.1007/s10257-010-0131-7
|View full text |Cite|
|
Sign up to set email alerts
|

Uncovering ITIL claims: IT executives’ perception on benefits and Business-IT alignment

Abstract: Over 45% of companies are estimated to use IT Service Management (ITSM) frameworks, yet, these frameworks can be imitated and hence the competitive advantage gained from these will quickly become obsolete. Therefore, research on the benefits of ITSM must focus on both operational and strategic benefits. An international survey of 441 firms was conducted to examine the benefits that IT Infrastructure Library (ITIL), the de-facto ITSM framework, provided to the IT organizations. The research focused on how (1) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 19 publications
0
37
0
1
Order By: Relevance
“…Moreover, it has been argued that organizations implementing ITIL framework may realize benefits in terms of increased customerculture and service as well as the efficiency and transparency of IT processes ( [40]). In a survey of 441 firms, [41]) examined the benefits of implementing ITIL as a framework for ITSM and provided a collection of nine key benefits at strategic and operational levels including: "service quality, standardization of service, customer satisfaction, return on investment, reduction of downtime, benefited from best practice experience of others, financial contribution control, first-call resolution rate, morale of IT" (table 1, p. 366). In our case study organizations, the ITIL project manager at GSP summarized the benefits realized from the implementations as "…we were able to map and document our processes, the customer service culture has improved, now we carry out a satisfaction survey after closing every incident, resolving a problem or fulfilling a request, the average score we have is over 86% satisfaction rate".The GSP ITIL project manager also added "after implementing ITIL the incident resolution time dropped to 45 minutes, we were able to overcome the communication problem, and the service desk has been established and widely advertised as a single point of contact".…”
Section: Itil Implementation Benefitsmentioning
confidence: 99%
“…Moreover, it has been argued that organizations implementing ITIL framework may realize benefits in terms of increased customerculture and service as well as the efficiency and transparency of IT processes ( [40]). In a survey of 441 firms, [41]) examined the benefits of implementing ITIL as a framework for ITSM and provided a collection of nine key benefits at strategic and operational levels including: "service quality, standardization of service, customer satisfaction, return on investment, reduction of downtime, benefited from best practice experience of others, financial contribution control, first-call resolution rate, morale of IT" (table 1, p. 366). In our case study organizations, the ITIL project manager at GSP summarized the benefits realized from the implementations as "…we were able to map and document our processes, the customer service culture has improved, now we carry out a satisfaction survey after closing every incident, resolving a problem or fulfilling a request, the average score we have is over 86% satisfaction rate".The GSP ITIL project manager also added "after implementing ITIL the incident resolution time dropped to 45 minutes, we were able to overcome the communication problem, and the service desk has been established and widely advertised as a single point of contact".…”
Section: Itil Implementation Benefitsmentioning
confidence: 99%
“…Marrone and Kolbe, for example, found that as the adoption to ITIL increased, the levels of maturity of the Business-IT alignment increased (Marrone and Kolbe 2010). Most benefits, however, are found to be operational.…”
Section: Benefits From Implementing Itilmentioning
confidence: 99%
“…Benefits from implementing ITIL were measured using a six-item scale adapted from Cater-Steel et al (2009) and Iden (2010), and by incorporating the overview of research on ITIL benefits as presented by Marrone and Kolbe (2010). Items chosen are ''customer satisfaction has been improved'', ''user satisfaction has been improved'', ''focus on IT services has been improved'', ''professional standard has been improved'', ''IT costs have been reduced'' and ''roles and responsibilities have been clarified''.…”
Section: Itil Project Benefitsmentioning
confidence: 99%
“…the contribution of Cater-Steel et al (2009) or the comprehensive international survey by Marrone and Kolbe (2011) which reports on the ever-increasing ITIL adoption and the increasing realized operational benefits caused by the usage of ITIL.…”
Section: Information Technology Infrastructure Library (Itil)mentioning
confidence: 99%